Análise das ações da Magazine Luiza (Magalu) pré e pós aquisição da Kabum - Octaviano, Ricardo Augusto (Universidade Federal de São Carlos, 2025)
The present work proposes an analysis of Magazine Luiza’s stocks in the context of the acquisition of Kabum, seeking to understand the variations in closing prices before and after the transaction. The study will be based on the implementation of a GARCH or ARCH model, aiming to identify volatility patterns and assess whether there have been significant changes in price behavior characteristics. The choice of these models is justified by their ability to capture volatility in time series data, making them suitable for analyzing changes in variability over time. The results indicate that Magalu’s stock behavior exhibited distinct patterns in the analyzed periods. Before the acquisition, the GARCH(1, 1) model was adequate for capturing volatility, whereas after the acquisition, the volatility structure became more complex, suggesting that external factors may have influenced the dynamics of returns. The decline in stock prices following the transaction may be related to variables not directly considered in this study, such as macroeconomic conditions or changes in investor perception.
Analysis of Magazine Luiza’s (Magalu) stock before and after the acquisition of Kabum
Keywords: ARCH; GARCH; Volatilidade; Volatility; Modelagem financeira; Kabum; Financial modeling; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::PROBABILIDADE E ESTATISTICA APLICADAS